Math, asked by rimimandal697, 7 months ago

intregation on
xdx/(x + 1)(2x + 1)

Answers

Answered by Anonymous
11

Answer:

(x + 1)(2x - 1)dx

=  \frac{2}{3} {x}^{3}  +  \frac{1}{2}  {x}^{2}  - x + c

Step-by-step explanation:

Find an antiderivative of a function is the same as finding the integral.

So we want to find

(x + 1)(2x  - 1)dx

2 {x}^{2}  + x - 1dx

To find this, we use the power rule

 {x}^{n} dx =  \frac{1}{n + 1}  {x}^{n}  + c

  => 2 {x}^{2} + x - 1dx

=  \frac{2}{3}  {x}^{3}  +  \frac{1}{2}  {x}^{2}  - x + c

Hope This Helps ☺

Answered by Anonymous
11

Solution

We Have

 \sf \implies \:  \int \dfrac{x}{(x + 1)(2x + 1)} dx \\

Using practical Fraction Method

 \sf \implies \:  \dfrac{x}{(x + 1)(2x + 1)}  =  \dfrac{A }{(x + 1)}  +  \dfrac{B}{(2x + 1)}

 \sf \implies \:  \dfrac{x}{(x + 1)(2x + 1)}  =  \dfrac{A(2x + 1) + B(x + 1)}{(x + 1)(2x + 1)}

 \sf \implies \:  \dfrac{x}{ \cancel{(x + 1)(2x + 1)}}  =  \dfrac{A(2x + 1) + B(x + 1)}{ \cancel{(x + 1)(2x + 1)}}

 \sf \implies \: x = A(2x + 1) +  B(x + 1)

When x = - 1

 \sf \implies \: - 1 = A(2 \times  - 1 + 1) +B ( - 1 + 1)

 \sf \implies \:  - 1 = A( - 1) + 0

 \sf \implies \: A = 1

When x = -1/2

 \sf \implies \:  \dfrac{ - 1}{2}  = A (2 \times  \dfrac{ - 1}{2}  + 1) + B \bigg( \dfrac{ - 1}{2}  + 1 \bigg)

 \sf \implies \:  \dfrac{ - 1}{2}  = 0 +  B \dfrac{1}{2}

 \sf \implies \:  B =  - 1

Now put the value A = 1 and B = - 1

 \sf \implies \:  \dfrac{x}{(x + 1)(2x + 1)}  =  \dfrac{A }{(x + 1)}  +  \dfrac{B}{(2x + 1)}

 \sf \implies \:  \dfrac{x}{(x + 1)(2x + 1)}  =  \dfrac{1 }{(x + 1)}  +  \dfrac{ - 1}{(2x + 1)}

 \sf \implies \int \bigg( \dfrac{1 }{(x + 1)}  +  \dfrac{ - 1}{(2x + 1)}  \bigg)dx \\

 \sf \implies \:  \int  \dfrac{1}{(x + 1)} dx +  \int \dfrac{ - 1}{(2x + 1)} dx \\

\sf \implies \:  \int  \dfrac{1}{(x + 1)} dx  -   \int \dfrac{ 1}{(2x + 1)} dx \\

 \sf \implies \: ln(x + 1) - \dfrac{1}{2}  ln(2x + 1) + c

Answer

\sf \implies \: ln(x + 1) - \dfrac{1}{2} ln(2x + 1) + c

Similar questions